Analyzing the English translation of People-Pleasing Behaviors mentioned in Tom Lembong’s Instagram Caption - Raden Roro Shinta Felisia (International Journal Multidisciplinary Science, 2025)
Instagram allows users to include captions of up to 2,200 characters beneath posted visual content, including images and videos. These captions provide a space for users to offer explanations, contextual information, or personal viewpoints related to the accompanying visuals. This research analyzes the English translation of people-pleasing behaviors mentioned in Tom Lembong’s Instagram caption. In the target language (English), there are two linguistic units: “reluctance to offend” and “fearing to offend.” These two translation units prioritize the intended meaning over preserving the original terms, which may result in deviations from the source terminology, thereby reflecting the use of paraphrasing. The researcher hopes that the findings of this study will contribute to the field of translation, particularly to the translation of behavioral terms.